Preparation method for regenerating waste lithium iron phosphate into ferric sodium pyrophosphate
By being separated and treated with lithium iron phosphate batteries, the use of oxides to promote the recycling of lithium and the regeneration of FEPO4 to prepare high -performance sodium phosphate materials to solve the problem of waste of resources and environmental pollution, and realize the efficient cycle of resources Utilize and improve material performance.
Patent Information
- Application Number
- CN202411497079.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
Improper treatment of waste lithium iron phosphate batteries will lead to waste of resources and environmental pollution, and the prior art will find it difficult to efficiently recover lithium and regenerate it into high-performance sodium iron pyrophosphate materials.
By separating the lithium iron phosphate orthopedic tape, mixed oxides and stirring or ultrasonic shock in acidic or alkaline solutions, and then sintering in an inert atmosphere, using endogenous free radical catalysis and oxide to promote the oxidation of LIFEPO4 and achieve lithium lithium Effective recycling and regeneration of FEPO4 finally prepared high -capacity sodium phosphate orthopedic materials.
The efficient recycling and regeneration of lithium iron phosphate is the material of high -performance sodium iron phosphate, reducing waste of resource and environmental pollution, and improving the circulating performance and energy density of the material.
Smart Images

Figure CN119370817A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material production, and specifically relates to a preparation method for regenerating waste lithium iron phosphate into sodium iron pyrophosphate. Background Art
[0002] In recent years, the new energy industry has continued to develop. Lithium-ion batteries (LIBs) have the advantages of high discharge voltage, long cycle life and no memory effect. They are widely used in portable electronic devices, electric vehicles and electrochemical energy storage. The rapid development of electric vehicles has led to the explosive growth of power batteries, and lithium iron phosphate batteries (LFPBs) have occupied a large market share with their good safety, low cost and non-toxicity. As a result, the amount of scrapped lithium iron phosphate batteries has also increased year by year. Waste lithium iron phosphate batteries contain a large amount of metal elements such as lithium, iron, aluminum, and copper. If they are not handled properly, it is not only a waste of precious resources, but also pollutes the environment. Therefore, recycling and regenerating waste lithium iron phosphate batteries is of great significance for protecting the environment and saving resources. Through recycling and regeneration technology, the metal materials in waste batteries can be extracted and reused to reduce resource waste and environmental pollution.
[0003] Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7) is a positive electrode material for sodium ion batteries with high energy density (129 mAh g -1 ), high average operating voltage (3.1VS.Na + / Na), low volume expansion (4% less), long cycle life and good safety. It is considered the most promising positive electrode material for sodium ion batteries. With the continuous development of new energy technologies, its application prospects as a battery material are also becoming increasingly broad. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a preparation method for regenerating waste lithium iron phosphate into sodium iron pyrophosphate, which can efficiently recover the lithium therein, and uses waste lithium iron phosphate as raw material to regenerate the iron and phosphorus elements therein into high-capacity sodium iron pyrophosphate with large capacity and excellent cycle performance.
[0005] To achieve the above object, the present invention first provides a method for preparing sodium iron pyrophosphate by regenerating waste lithium iron phosphate, comprising the following steps:
[0006] S1. Separate the waste lithium iron phosphate positive electrode sheets, remove the current collector, and obtain a powdery or sheet-like pure phase lithium iron phosphate positive electrode recycling material;
[0007] S2, mixing the lithium iron phosphate positive electrode recovery material obtained in step S1 with the oxide, adding deionized water, adjusting the pH with an acidic solvent or an alkaline solution, stirring or ultrasonically shaking the reaction, filtering, washing, and drying the obtained product to obtain an oxide slag containing an iron source compound;
[0008] S3, adding a sodium source and a phosphorus source to the oxide slag obtained in step S2, mixing the mixture, sintering the mixture in an inert gas atmosphere, and cooling the mixture to obtain a sodium iron pyrophosphate positive electrode material;
[0009] The oxide is selected from one or more of hydrogen peroxide, sodium persulfate, peroxydisulfate and ozone.
[0010] Preferably, the waste lithium iron phosphate positive electrode sheet in step S1 is selected from a lithium iron phosphate electrode sheet containing PVDF, a conductive agent, a current collector aluminum foil, and a positive electrode material active substance.
[0011] Preferably, in step S2, the mass ratio of the lithium iron phosphate positive electrode recovery material to the oxide is 1:1-2.
[0012] Preferably, in step S2, an acidic solvent is used to adjust the pH to 2-6, and an alkaline solution is used to adjust the pH to 10-12.
[0013] Preferably, in step S2, the solid-to-liquid ratio of the lithium iron phosphate positive electrode recovery material and oxide mixture to deionized water and acidic solvent or alkaline solution is 1 kg: 1-4 L.
[0014] Preferably, the stirring or ultrasonic oscillation reaction temperature in step S2 is 50-90° C., and the reaction time is 20-210 min.
[0015] Preferably, in step S3, the sodium source is selected from one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate; the phosphorus source is selected from one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
[0016] Preferably, the mixing method in step S3 is ball milling or aqueous solution dissolution. After the sodium source and phosphorus source are added, the molar ratio of Na element, P element and Fe element in the oxidized slag in step S2 is 4:4:2.5-3.
[0017] Preferably, the inert atmosphere in step S3 is nitrogen or argon.
[0018] Preferably, the sintering conditions in step S3 are: keeping warm at 350°C for 1 to 4 hours in the first stage, keeping warm at 500°C to 600°C for 8 to 20 hours after pressing into a solid sheet, with a heating rate of 5 to 10°C / min and a cooling rate of 5 to 15°C / min.
[0019] The mechanism of preparing sodium ferric pyrophosphate in this scheme is as follows:
[0020] The oxide used in this scheme is sodium persulfate Na2S2O8. Adding a small amount of Na2S2O8 can generate free radicals through the endogenous catalytic activation of LiFePO4. In addition, the energy provided by heating can cause the cleavage of the OO bond in Na2S2O8, promoting SO4 ·- The generation of SO4 ·- LiFePO4 is further oxidized to selectively leach Li and recover FePO4. The reaction equation is as follows:
[0021] LiFePO4+S2O8 2- →FePO4+SO4 ·- +SO4 2 +Li +
[0022] SO4 ·- +H2O→HSO4 - + OH(k=500M -1 s -1 )
[0023] SO4 ·- +SO4 ·- →2SO4 2- (k=8.9×10 8 M -1 s -1 )
[0024] SO4 ·- +S2O8 2- →S2O8 ·- +SO4 2- (k=6.1×10 5 M -1 s -1 )
[0025] LiFePO4+SO4 ·- →FePO4+SO4 2- +Li +
[0026] 2LiFePO4+S2O8 2 →2FePO4+2SO4 2- +2Li +
[0027] The process of regeneration using iron phosphate as raw material usually involves the reduction of trivalent iron phosphate. In the oxidized slag obtained by recycling waste lithium iron phosphate raw materials, in addition to iron phosphate, there are 10wt% coated carbon and a small amount of conductive agent added in the process of making pole pieces. The unique advantages of waste lithium iron phosphate raw materials are brought into play with it as a reducing agent. This scheme uses a wet method as a treatment, and the electrolyte is dissolved in an acid solution to retain the carbon. The conductive carbon in the waste lithium iron phosphate is used as a reducing agent without the need for an external reducing agent or a carbon source to obtain a high-performance sodium iron phosphate pyrophosphate positive electrode material, and most of the lithium is extracted into the filtrate to complete the high-purity separation of iron and lithium, and achieve complete recovery of lithium.
[0028] At the same time, in this solution, the coated carbon carried by the iron phosphate itself will be distributed more evenly during the ball milling process, and less impurities will be generated.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) Compared with the prior art, this method uses the original coated carbon in waste lithium iron phosphate as raw material, does not require an additional carbon source, innovates in the direction of raw material synthesis and product performance, and regenerates waste lithium iron phosphate into high-performance sodium iron pyrophosphate, thereby achieving a circular and efficient utilization of resources.
[0031] (2) In the prior art, calcination is used to directly burn away impurities such as electrolytes, but this scheme uses a wet method as a treatment, and the electrolyte is dissolved in an acid solution, so that the carbon can be retained. The conductive carbon in the waste lithium iron phosphate is used as a reducing agent without the need for an external reducing agent, thereby obtaining a high-performance sodium iron pyrophosphate positive electrode material, and most of the lithium is extracted into the filtrate, completing the high-purity separation of iron and lithium, and realizing the complete recovery of lithium.
[0032] (3) Compared with the existing technology of regenerating lithium iron phosphate into battery positive electrode materials, this scheme does not require an impurity removal process for the regeneration of sodium iron phosphate pyrophosphate, a positive electrode material for sodium ion batteries. The impurity removal step is required in the process of recycling waste lithium iron phosphate to regenerate lithium ion battery positive electrode materials. In this scheme, all the components of sodium compounds in the process of preparing sodium iron pyrophosphate phosphate, trace sulfate ions are subsequently sintered into trace sodium iron sulfate phases with electrochemical activity, which has no effect on the performance of sodium ion battery positive electrode materials. In this scheme, the recycled slag obtained in the recycling process is mainly high-purity iron phosphate. The specific implementation of controlling the solid-liquid ratio, temperature, and reaction time in the recycling process can control the impurity content to less than 0.1%.
[0033] (4) This scheme recycles waste lithium iron phosphate into sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7), which can not only reduce pollutants and protect the environment, but also save resources and alleviate resource shortages. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 The microstructure of the regenerated sodium iron pyrophosphate of Experimental Example 1 was tested by scanning electron microscopy (SEM);
[0036] Figure 2 is the XDR diagram of sodium iron pyrophosphate in Experimental Example 1;
[0037] Figure 3 The first cycle charge and discharge results of the button half-cell at 0.1C rate in Experimental Example 1;
[0038] Figure 4 This is the XRD pattern of the regenerated sodium iron pyrophosphate of Experimental Example 1;
[0039] Figure 5 These are the first 150 charge and discharge cycles of the button-type half-cell at 1C rate in Experimental Example 1. DETAILED DESCRIPTION
[0040] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0041] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0042] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art; unless otherwise specified, the reagents used in the examples are commercially available.
[0043] Example 1
[0044] Regeneration of waste lithium iron phosphate into sodium iron pyrophosphate
[0045] S1. Retired lithium iron phosphate batteries are all recycled waste batteries. During the disassembly process, the positive electrode sheet and the negative electrode sheet are first disassembled, and the positive electrode material and the current collector are completely separated to obtain a pure phase positive electrode material;
[0046] S2, 3 kg of lithium iron phosphate positive electrode material and 5 kg of sodium persulfate were mixed in 20 L of deionized water, 0.5 mol / L of sulfuric acid was added to adjust the pH to 4, and the mixture was stirred and heated at 90° C. for 60 minutes, filtered, washed and dried to obtain an oxide slag containing an iron source compound;
[0047] S3, mixing the oxidized slag with ammonium dihydrogen phosphate and sodium carbonate, with the sodium iron phosphorus molar ratio being 4:2.5 to 3:4 after addition, wet ball milling at 600 rpm for 12 h to mix, keeping the obtained precursor at 350°C for 3 h under nitrogen atmosphere, heating to 550°C at 5°C / min and keeping it for 15 h, and cooling to room temperature at a rate of 5°C / min to obtain sodium iron pyrophosphate positive electrode material;
[0048] Example 2
[0049] Regeneration of waste lithium iron phosphate into sodium iron pyrophosphate
[0050] In step S2, 1 wt% of carbon nanotubes as a conductive agent are added, and the remaining steps are the same as those in Example 1.
[0051] Example 3
[0052] Regeneration of waste lithium iron phosphate into sodium iron pyrophosphate
[0053] The oxidant sodium persulfate in Example 1 was replaced with ozone, and an ozone generator was used to carry out oxidation for 10 minutes at pH = 6.5 and an oxygen flow rate of 1 L / min. The remaining steps were the same as in Example 1.
[0054] Example 4
[0055] Regeneration of waste lithium iron phosphate into sodium iron pyrophosphate
[0056] In Example 1, a 0.5 mol / L NaOH solution was added to adjust the pH to 10, and the other steps were the same as in Example 1.
[0057] Example 5
[0058] S1. Retired lithium iron phosphate batteries are all recycled waste batteries. During the disassembly process, the positive electrode sheet and the negative electrode sheet are first disassembled, and the positive electrode material and the current collector are completely separated to obtain a pure phase positive electrode material;
[0059] S2, 3 kg of lithium iron phosphate positive electrode material and 5 kg of sodium persulfate were mixed in 20 L of deionized water, sulfuric acid was added to adjust the pH to 4, and the mixture was stirred and heated at 90° C. for 60 minutes, filtered, washed and dried to obtain an oxide slag containing an iron source compound;
[0060] S3, mixing the oxidized slag with ammonium dihydrogen phosphate and sodium carbonate, with the sodium iron phosphorus molar ratio of 4:2.5 to 3:4 after adding, wet ball milling at 600rpm for 12h to mix, keeping the obtained precursor at 350℃ for 3h under nitrogen atmosphere, compacting into sheets and then sintering for the second time, heating to 600℃ at 10℃ / min and keeping it for 20h, cooling to room temperature at 15℃ / min to obtain sodium iron pyrophosphate positive electrode material;
[0061] Comparative Example 1
[0062] Wet process for preparing battery grade iron phosphate
[0063] S1. Retired lithium iron phosphate batteries are all recycled waste batteries. During the disassembly process, the positive electrode and the negative electrode are first disassembled;
[0064] S2. Stir the positive electrode powder in a 5% sodium hydroxide solution for 2 hours, wash and filter, and then roast in air at 500° C. for 3 hours to obtain an intermediate product containing lithium, iron and phosphorus.
[0065] S3, 3 kg of the product obtained in S2 and 3 kg of hydrogen peroxide were mixed in 20 L of deionized water, the pH was adjusted to 4.5 acidic conditions with dilute sulfuric acid, and the reaction was carried out for 60 minutes. The obtained product was filtered, washed, dried, and then impurities were removed by cation exchange adsorption to obtain battery-grade iron phosphate.
[0066] Preparation of Sodium Ferric Pyrophosphate from Battery Grade Ferric Phosphate
[0067] S3. Mix the iron source ferric phosphate, the phosphorus source diammonium phosphate, the sodium source sodium carbonate and the carbon source glucose, the elemental substance ratio of Na:Fe:P=4:3:4, sinter at 600°C in a nitrogen atmosphere, and cool to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0068] Comparative Example 2
[0069] Preparation of Sodium Ferric Pyrophosphate by Spray Drying
[0070] S1, sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and ascorbic acid are dissolved in 20L deionized water according to the molar ratio of 4:3:4:1.2, 2kg of sodium carbonate is added, ascorbic acid is added to prevent the divalent iron from being oxidized, stirred evenly, and concentrated by pyrolysis to obtain a supersaturated ion solution;
[0071] S2. The above solution is spray-dried at a feed rate of 50 mL / min, an air inlet temperature of 400° C., a reaction temperature in the chamber of 390° C., an air outlet temperature of 370° C., and a rapid reaction of 12 h to obtain sodium iron pyrophosphate.
[0072] Experimental Example 1
[0073] The performance of the sodium iron phosphate pyrophosphate positive electrode material obtained in the examples and comparative examples was investigated
[0074] The materials obtained in Example and Comparative Example 1 were sieved, slurried and prepared into sheets, and their electrochemical properties were tested.
[0075] (1) Scanning electron microscopy images of the regenerated sodium iron pyrophosphate prepared in Example 1 and Comparative Example 1
[0076] The microstructure of the sodium iron phosphate pyrophosphate prepared in Example 1 and the sodium iron phosphate pyrophosphate prepared in Comparative Example 1 was tested by scanning electron microscopy (SEM). Figure 1 As shown, the XRD pattern is Figure 2 As shown, the results show that by comparing the intensity of the characteristic peaks (220) and (031) of sodium iron phosphate NaFePO4 of Example 1 and Comparative Example 1, it can be seen that Example 1 contains less impurities in sodium iron phosphate NaFePO4 than Comparative Example 1, and the mixture is more uniform. This is because the ferrophosphorus is more evenly mixed with sodium sulfate impurities and carbon during the lithium extraction mixture, and is more fully reduced, so fewer impurities are generated.
[0077] (2) Investigation of the element content of the slag in Example 1
[0078] The ICP-OES test of the element content of the oxidized slag obtained in step S2 of Example 1 is shown in Table 1 below. The results show that the lithium ion extraction rate reaches more than 99%, and the phosphorus-iron ratio of the constituent phase is 1:1.
[0079] Table 1 Analysis of element content of iron pyrophosphate in regenerated phosphoric acid in Example 1
[0080]
[0081] (3) First cycle charge and discharge of button-type half-cells of Example 1-2 and Comparative Example 1-2 at 0.1C rate
[0082] The results are as follows Figure 3 As shown, the results show that the regenerated sample prepared in Example 1 has equivalent charge and discharge performance to the standard sample prepared in Comparative Examples 1-2. The sample recovered in Example 1 using waste lithium iron phosphate as raw material without adding additional carbon source can still achieve almost the same charge and discharge performance as the standard sample. After adding the conductive agent, Example 2 has a larger charge and discharge capacity in the first cycle. Additional conductive agent can be added according to the scenario to improve the charge and discharge performance of the material.
[0083] (4) XRD test of the regenerated sample of Example 1
[0084] The results are as follows Figure 4 As shown, the results show that the regenerated sample has a sodium iron pyrophosphate crystal structure, which is sodium iron pyrophosphate.
[0085] (5) Examining the first 150 cycles of charge and discharge at 1C rate of the button-type half-cells of Example 1-2 and Comparative Example 1-2
[0086] The results are as follows Figure 5 As shown, the results show that the cycle stability of the regenerated samples prepared by this scheme is almost the same as that of the standard samples prepared in comparative examples 1-2. The sample recovered in Example 1 using waste lithium iron phosphate as raw material without adding additional carbon source can still achieve a cycle stability similar to that of the standard sample. The cycle performance of Example 2 is more stable after adding a conductive agent. Additional conductive agents can be added according to the scenario to improve the cycle performance of the material.
[0087] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing sodium iron pyrophosphate by regenerating waste lithium iron phosphate, characterized in that: The following steps are involved: S1. Separate the waste lithium iron phosphate positive electrode sheets, remove the current collector, and obtain a powdery or sheet-like pure phase lithium iron phosphate positive electrode recycling material; S2, mixing the lithium iron phosphate positive electrode recovery material obtained in step S1 with the oxide, adding deionized water, adjusting the pH with an acidic solvent or an alkaline solution, stirring or ultrasonically shaking the reaction, filtering, washing, and drying the obtained product to obtain an oxide slag containing an iron source compound; S3, adding a sodium source and a phosphorus source to the oxide slag obtained in step S2, mixing the mixture, sintering the mixture in an inert gas atmosphere, and cooling the mixture to obtain a sodium iron pyrophosphate positive electrode material; The oxide is selected from one or more of hydrogen peroxide, sodium persulfate, peroxydisulfate and ozone.
2. The preparation method according to claim 1, characterized in that: In the step S1, the waste lithium iron phosphate positive electrode sheet is selected from a lithium iron phosphate electrode sheet containing PVDF, a conductive agent, a current collector aluminum foil, and a positive electrode material active substance.
3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the lithium iron phosphate positive electrode recovery material to the oxide is 1:1-2.
4. The preparation method according to claim 1, characterized in that: In step S2, an acidic solvent is used to adjust the pH to 2-6, and an alkaline solution is used to adjust the pH to 10-12.
5. The preparation method according to claim 1, characterized in that: In the step S2, the solid-to-liquid ratio of the lithium iron phosphate positive electrode recovery material and oxide mixture to deionized water and acidic solvent or alkaline solution is 1kg:1-4L.
6. The preparation method according to claim 1, characterized in that: The stirring or ultrasonic oscillation reaction temperature in step S2 is 50-90° C., and the reaction time is 20-210 min.
7. The preparation method according to claim 1, characterized in that: In step S3, the sodium source is selected from one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate; the phosphorus source is selected from one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate, sodium hydroxide, sodium formate, sodium citrate, sodium pyrophosphate, and sodium dihydrogen pyrophosphate.
8. The preparation method according to claim 1, characterized in that: The mixing method in step S3 is ball milling or aqueous solution dissolution. After the sodium source and phosphorus source are added, the molar ratio of the Na element, the P element and the Fe element in the oxidized slag in step S2 is 4:4:2.5-3.
9. The preparation method according to claim 1, characterized in that: The inert atmosphere in step S3 is nitrogen or argon.
10. The preparation method according to claim 1, characterized in that: The sintering conditions in step S3 are as follows: the first stage is 350° C. for 1 to 4 hours, and after being pressed into a solid sheet, the temperature is directly kept at 500° C. to 600° C. for 8 to 20 hours, the heating rate is 5 to 10° C. / min, and the cooling rate is 5 to 15° C. / min.
Citation Information
Cited By
Method for producing ferric sodium pyrophosphate and extracting lithium from lithium iron phosphate black powder through replacement
CN120172383A
System and method for recycling iron phosphate and battery-grade lithium phosphate from waste lithium iron phosphate
CN120423510A
Method for preparing iron phosphate by using waste ferric sodium pyrophosphate
CN121651312A
Battery preparation method based on sodium ferric pyrophosphate regenerated material and hard carbon regenerated material
CN122393461A
Battery preparation method based on sodium pyrophosphate iron regeneration material and hard carbon regeneration material
CN122393461B
